Characterization of temporomandibular dysfunction in students of the graduation of a higher Education Institution of Alagoas / Caracterização da disfunção temporomandibular em estudantes da graduação de uma instituição de Ensino Superior de Alagoas - Joyceane Alves de Oliveira; Alexsandra de Souza Pedrosa; Ana Candice Coêlho; Djanira Florentino Silva; Camila Maria Beder Ribeiro Girish Panjwani (Universidade Estadual de Alagoas, 2019)
The TMJ participates in important roles of the stomatognathic system, its disharmony is impaired. We aim to characterize the temporomandibular dysfunction of undergraduate students of a higher education institution in Alagoas. It is a discretionary, observational, cross-sectional and quantitative study, composed by students from HEI, were students between 18 and 29 years old, enrolled regularly. Individuals with spinal problems, rheumatic diseases or any other condition that influenced joint health were excluded. Instructed to sign the TCLE, answer the Fonseca Anamnestic Questionnaire, and the Index of mandibular cranial dysfunction (IDCCM) + mandibular mobility index - IMM. Statistical analysis was performed using the chi-square test with significance of 95%. The sample consisted by 226 participants, 76% female, 24% male. 73.9% of the students presented some degree of TMD, where 45.6% of the mild type, 22.1% moderate and 6.2% severe (p = 0.1365). Medicine was the course that less affected. The TMD did not present significance with mobility p = 0.1603. According to Helkimo, at least two symptoms (pain, noise, decreased range of motion) were evidenced in the students, not necessarily the same presenting the pathological condition to report the symptom. More than 70% of the studied population presented TMD, proposes more studies that characterize TMD, and traces a clinical profile of this pathology, to implement appropriate treatment and that is effective in the young, increasingly early in order to decrease its incidence in adult life.